Securix: a 3D game-based learning approach for phishing attack awareness. Issue 2 (3rd April 2019) - Onashoga, Adebukola S.; Ojo, Oluwafolake E.; Soyombo, Oluwadamilola O.
ABSTRACT: Majority of Internet users lack anti-phishing skills in identifying a phishing attack. This paper introduces a 3D-game prototype named Securix which simplifies and exaggerates real life scenario and conveys different game design principles. Securix is divided into three levels, depicted in scenarios, namely: URL, E-mail and Website which addresses different types of phishing attack. 3D characters and tools were designed to be imported into the game engine using C# programming language for scripting. A Technology Acceptance Model was used for evaluation of the game. To ascertain the liability and acceptability of this design, 50 questionnaires were administered. The results revealed perceived usefulness as the most significant determinant of adoption of Securix than all the other variables. All the relationships between Perceived Ease Of Use (PEOU), Perceived Usefulness (PU), Attitude Towards Using (ATU), and Actual Usage of the System (AUOS) were tested and found to be significant and positive. Analysis from the questionnaire revealed that PU was a strong predictor of actual usage with ninety-five percent (95%) of users as compared to PEOU which was sixty-eight percent (68%) and AUOS which had a result of seventy-four percent (74%). The overall game design enhances the user's avoidance behaviour through motivation to protect themselves against phishing threats.